The Threat of Cultural Degradation Due to Tourism Activities (Case Study on Tourist Guides from Baduy Dalam Tribe at Banten, Indonesia) - Pradana, Triandi; Simamora, Vera Inne Juni; Zai, Yanna Mesra Indah (Yayasan Ilomata, 2024)
With the inclusion of Baduy in the list of Rural Tourism, it also brings tourists with the habits they bring. Tourism needs and tourist behavior such as bringing mobile phones, taking pictures are feared to affect and are considered to threaten the purity of teachings and beliefs in Baduy. The novelty of this research is to fill the gap of existing problems or a void of knowledge, lack of literature that focuses on the Threat of Cultural Degradation because of the existence of Baduy Dalam Tribe Residents who have activities as tour guides, and they are suspected of having cell phones and Instagram social media which are considered contrary to the customary rules of the Baduy Tribe. The research method used is qualitative with a case study approach. Data collection through interviews, observation and documentation. The data obtained will be analyzed using the Miles & Huberman interactive model. Baduy customary rules strictly prohibit the use of technology, but local guides from the Baduy Dalam tribe are found using mobile phones and Instagram social media to attract tourists to use their services. There is a social change in local guides as they adjust to the needs of tourists. They use this technology secretly because they realize that they have violated customary rules. The customary leader explained that what happened to the local guide had indirectly violated customary rules. The conclusion of this research is that there is a threat of cultural degradation due to tourism activities, especially for tour guides from the Baduy Dalam Tribe. Mobile phone ownership and the use of Instagram social media to attract tourists to use guiding services are considered contrary to customary rules.